Challenges to detect glaucomatous visual field loss with pupil perimetry [Corrigendum] - Asakawa K (Dove Medical Press, 2019)
Asakawa K and Shoji N. Clin Ophthalmol. 2019;13:1621–1625.On page 1622, 3rd paragraph from the left hand column, the sentence “Based on our previous study,8 in the 36 test points, the sensitivity of the seventh highest point when compared with the normal value was used as the standard degree of sensitivity for the entire visual field. The pattern deviation (85th percentile) of the pupil field was calculated as a value representing the difference between age-matched normal and abnormal percentage pupil constriction.” should read “Based on our previous study,8 in the 36 test points, the sensitivity of the fifth highest point when compared with the normal value was used as the standard degree of sensitivity for the entire visual field. The pattern deviation (85th percentile) of the pupil field was calculated as a value representing the difference between age-matched normal and abnormal percentage pupil constriction.”  Following a review of our data post-publication, we found the incorrect calculation for the 36 test points with the 85th percentile value of pupil perimetry which should read fifth highest point instead.In the 36 points, the 85th percentile value of pupil perimetry was calculated as follows:36×0.85=30.636−30.6=5.4The authors apologize for this error.   Read the original article